A Comparison of Genicular Nerve Blockade With Corticosteroids Using Either Classical Anatomical Targets vs Revised Targets for Pain and Function in Knee Osteoarthritis: A Double-Blind, Randomized Controlled Trial. Issue 5 (27th March 2021) - Fonkoue, Loïc; Steyaert, Arnaud; Kouame, Jean-Eric K; Bandolo, Eric; Lebleu, Julien; Fossoh, Hermann; Behets, Catherine; Detrembleur, Christine; Cornu, Olivier
Abstract: Objective: Compare the effectiveness of genicular nerve blockade (GNB) using classical anatomical targets (CT) versus revised targets (RT) in patients suffering from chronic knee osteoarthritis pain. Design: Double-blinded randomized controlled trial. Setting: Pain medicine center of a teaching hospital. Methods: We randomly assigned 55 patients with chronic knee osteoarthritis pain to receive a GNB (using a fluid mixture of 2 mL: lidocaine 1% + 20 mg triamcinolone) with either classical targets (CT-group, n  = 28) or revised targets (RT-group, n  = 27). Numeric rating pain scale (NRS), Oxford knee score (OKS), Western Ontario and McMaster Universities osteoarthritis index score (WOMAC), Quantitative analgesic questionnaire (QAQ) and global perceived effects were assessed at baseline, and at 1-hour, 24-hours, 1, 4, and 12 weeks post-intervention. Results: The RT-group showed greater reduction in NRS mean score at 1-hour post-intervention (2.4 ± 2.1 vs 0.4 ± 0.9, 95% confidence interval (CI) [.0–.8] vs [1.6–3.2], P  <   .001). The proportion of patients achieving more than 50% knee pain reduction was higher in the RT-group at each follow up interval, yet these differences were statistically significant only at 1-hour post intervention (82.1% [95% CI = 63.1–93.9] vs 100% [95% CI = 97.2–100] P =  .02). Both protocols resulted in significant pain reduction and joint function improvement up to 12 weeks post-intervention. Conclusions: The revised technique allowed more pain relief as well as greater proportion of successful responders at 1-hour post intervention. The large volume injected during therapeutic GNB could have compensated the lack of precision of the classical anatomical targets, mitigating differences in outcomes between both techniques.